MANAJEMEN KEPALA SEKOLAH DALAM PENGELOLAAN LEMBAGA PENDIDIKAN ANAK USIA DINI DI TK YWKA KELURAHAN DEMANGAN KECAMATAN GONDOKUSUMAN YOGYAKARTA - Miftahurrusydi (Jurnal Studi Islam Lintas Negara (Journal of Cross-Border Islamic Studies), 2020)
The success of educational institutions, especially early childhood education, depends on the principal. The role of the principal as the leader of the institution must be able to bring the institution to achieve the goals that have been set together and take full responsibility for the smoothness and success of all matters of school management and management. This means, the principal must know and be able to implement the functions and aspects of management such as planning, organizing, leading and monitoring as well as aspects in management such as human resources, finance, community relations and marketing. The results of this research are; First, the management function implemented in the YWKA TK institution is carried out through the stages of planning, organizing, mobilizing and controlling. Broadly speaking, the YWKA TK institution at the initial stage held a large meeting to discuss what would be planned to be carried out later. Any plans that have been completed will be coordinated back to the foundation and committee. And will be evaluated in stages according to the conditions that occur in the institution. Second, management aspects implemented in YWKA TK institutions such as financial management, public relations and marketing are still not fully realized. Because in the management of public relations all unit assignments are still held by foundations and committees located at the central YWKA TK institution. Meanwhile, the agency's marketing management is still lacking because it has not implemented open marketing